Open Source as a Signalling Device - An Economic Analysis - Samuel Lee; Nina Moisa; Marco Weiß (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2003)
Open source projects produce goods or standards that do not allow for the appropriation of private returns by those who contribute to their production. In this paper we analyze why programmers will nevertheless invest their time and effort to code open source software. We argue that the particular way in which open source projects are managed and especially how contributions are attributed to individual agents, allows the best programmers to create a signal that more mediocre programmers cannot achieve. Through setting themselves apart they can turn this signal into monetary rewards that correspond to their superior capabilities. With this incentive they will forgo the immediate rewards they could earn in software companies producing proprietary software by restricting the access to the source code of their product. Whenever institutional arrangements are in place that enable the acquisition of such a signal and the subsequent substitution into monetary rewards, the contribution to open source projects and the resulting public good is a feasible outcome that can be explained by standard economic theory.
urn:nbn:de:hebis:30-17962
Keywords: D82; L14; L86; O31; 330; career concerns; economics of organization; open source software; signalling; Softwareentwicklung; IT-Berufe; Signalling; Erwerbsverlauf; Theorie; Open Source